2D Numerical investigation of surface wettability induced liquid water flow on the surface of the NACA0012 airfoil. (March 2023) - Sun, Haoyang; Lin, Guiping; Jin, Haichuan; Guo, Jinghui; Ge, Kun; Wang, Jiaqi; He, Xi; Wen, Dongsheng
Abstract: The accumulation of ice on wind turbine blades is a serious threat to the safety of wind power generation. Anti-icing techniques with low energy consumption, especially when combined with superhydrophobic surfaces, have recently attracted increasing levels of interest. In this work, the anti-icing mechanism of superhydrophobic surfaces was investigated by conducting the two-dimensional numerical analysis of the flow patterns of liquid water on surfaces with different wettability, which was based on the phase field method (PFM) and a dynamic contact angle (DCA) model. It is found that the wettability of surfaces significantly influences the flow, break, and shedding behaviors of liquid water on the surfaces. An increase in contact angle (CA) leads to more frequent break and shedding behaviors, and the flow pattern of liquid water gradually transformed from continuous water film to fragmented droplets because of the vortical flow field. In addition, it is also investigated that when the CA of surfaces exceeded 145°, the broken liquid water completely shed away in 0–0.1 chord length. Moreover, the average chordwise location ( x ‾ /c) and maximum chordwise location ( x max /c) of the liquid water that had traveled the farthest on the surface in 30 ms gradually decreased with increasing contact angle, which is beneficial to superhydrophobic-dry anti-icing. What's important, the wettability characteristics should be responsible for the unique water flow patterns coupled with shear stress, which has been validated again, and previously proposed by our work. The results of this study provide theoretical support for the incorporation of superhydrophobic surfaces in anti-icing technology applied to wind turbine blades, which is promising for solving the icing issue of wind turbine blades with low energy consumption.